Intensity limits for propagation of 0.527 microm laser beams through large-scale-length plasmas for inertial confinement fusion. - Niemann, C; Divol, L; Froula, D; Gregori, G; Jones, O; Kirkwood, R; Mackinnon, A; Meezan, N; Moody, J; Sorce, C; Suter, L; Bahr, R; et al. (2005)
We have established the intensity limits for propagation of a frequency-doubled (2omega, 527 nm) high intensity interaction beam through an underdense large-scale-length plasma. We observe good beam transmission at laser intensities at or below 2x10(14) W/cm(2) and a strong reduction at intensities up to 10(15) W/cm(2) due to the onset of parametric scattering instabilities. We show that temporal beam smoothing by spectral dispersion allows a factor of 2 higher intensities while keeping the beam spray constant, which establishes frequency-doubled light as an option for ignition and burn in inertial confinement fusion experiments.